Optical properties of thin film Sb2Se3 and identification of its electronic losses in photovoltaic devices. (1st November 2021) - Jayswal, Niva K.; Rijal, Suman; Subedi, Biwas; Subedi, Indra; Song, Zhaoning; Collins, Robert W.; Yan, Yanfa; Podraza, Nikolas J.
Graphical abstract: Highlights: Physically realistic complex dielectric function (ε) model developed for Sb2 Se3 . 1.12 eV indirect bandgap and 21.1 meV Urbach energy measured. External quantum efficiency (EQE) of Sb2 Se3 PV simulated using measured ε. Optical and electronic losses are identified from measured and simulated EQE. ∼440 nm carrier collection length identified in CdS/Sb2 Se3 heterojunction from EQE. Abstract: Sb2 Se3 has become a promising absorber layer material for photovoltaic applications because of its attractive optical properties and rapid improvement in Sb2 Se3 solar cell efficiency in recent years. The indirect bandgap and Urbach energy of Sb2 Se3 have been determined to be 1.12 eV and 21.1 meV, respectively, using photothermal deflection spectroscopy. Above bandgap critical points at 1.48, 2.00, 2.35, 2.87, and 3.86 eV are identified from the complex dielectric function ( ε = ε 1 + i ε 2 ) spectra of thin film Sb2 Se3 obtained from spectroscopic ellipsometry. Spectra in ε serve as input for external quantum efficiency (EQE) simulations of substrate type Sb2 Se3 solar cells. Comparison of experimental and simulated EQE quantifies carrier collection losses and identifies a carrier collection length in the absorber layer of 439 ± 4 nm and a 96.4 ± 0.2 % carrier collection probability near the heterojunction.